Reduce pollution, establish protected areas, manage fisheries properly? How to protect coral reefs based on carbon trading - Bai, Yuntao; Hu, Ruidi; Wang, Lan; Li, Delong (Frontiers in Marine Science, 2024)
As coral reefs around the world have suffered serious damage, it is necessary to protect them. Common modes of coral reef protection include reducing pollution, setting up reserves and managing fisheries rationally. In order to derive the applicable scope of various protection modes for coral reefs, this article constructs three differential game models and compares and analyzes the equilibrium results obtained by the models. Finally, the study shows that whether for developed or developing countries, when the benefits of coral reef treatment are small, the mode of reducing pollution can achieve the maximum benefit. As the benefits of coral reef treatment gradually increase, the mode of setting up nature reserves can achieve the maximum benefit. It is worth noting that the greater the carbon emission rights obtained by the number of coral reefs, the greater the benefits of coral reef treatment, the more likely developed countries will adopt the mode of setting up reserves.